Revitalisasi Posyandu Remaja: Strategi Peningkatan Kesehatan dan Pencegahan Pernikahan Dini - Widiastuti, KH Endah; Rosalinna, Rosalinna (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
In Sukorejo Village, Puhpelem District, Wonogiri Regency, early marriage is still a major problem. This is exacerbated by the lack of function of the Youth Posyandu as an institution that helps teenagers get health education. The purpose of this community service program is to revive the Youth Posyandu through an educational approach, cadre training, and health checks. Counseling, simulation, and pre-post test evaluation were used. The results showed an increase in participant understanding scores by 44.9%, the formation of an active youth cadre structure, and the formation of a regular Posyandu schedule. In addition, 76% of participants stated that they wanted to participate actively, and 89% of them acknowledged the impact of early marriage. This program shows that a participatory and character-based approach to teenagers is effective in increasing health awareness and preventing early marriage. These results are very important as a community-based intervention model that can be applied elsewhere..